Critically appraised topic on adverse food reactions of companion animals (9): time to flare of cutaneous signs after a dietary challenge in dogs and cats with food allergies - Thierry Olivry; Ralf S. Mueller (BMC Veterinary Research, 2020)
Abstract Background At this time, elimination diets followed by oral food challenges (OFCs) represent the “gold standard” for diagnosing skin-manifesting food allergies (FA) in dogs and cats. Regrettably, there is no clear consensus on how long one should wait for clinical signs to flare after an OFC before diagnosing or ruling-out a FA in a dog or a cat. Results We searched two databases on October 23, 2019 to look for specific information on the time for a flare of clinical signs to occur during OFCs after elimination diets in dogs and cats with skin-manifesting FAs. Altogether, we reviewed the study results of nine papers that included 234 dogs and four articles containing data from 83 cats. As multiple OFCs could be done in the same patient and not all animals included were subjected to an OFC, we were able to compile 315 and 72 times to flare (TTF) after an OFC in dogs and cats, respectively. When regrouping all cases together, about 9% of dogs and 27% of cats exhibited a flare of clinical signs in the first day after an OFC; 21% of dogs and 29% of cats had such relapse by the end of the second day. The time needed for 50 and 90% of dogs to exhibit a deterioration of clinical signs (TTF50 and TTF90) was 5 and 14, respectively; in cats, these times were 4 and 7 days, respectively. By 14 days after an OFC, nearly all food-allergic patients from both species had had a relapse of clinical signs. These results are limited by the likely under-reporting of flares that occur on the first day immediately following an OFC, the time in which IgE-mediated acute allergic reactions typically develop. Conclusion Veterinary clinicians performing an OFC need to wait for 14 and 7 days for more than 90% of dogs and cats with a skin-manifesting FA to have a flare of clinical signs, respectively.